Discussion on Ethical Conflicts and Regulations Regarding the Abuse of Visual Recognition Systems in Public Spaces - Zhang, Xiufeng; Lin, Xintong (Innovative Applications of AI, 2025)
Against the background of frequent abuse of visual recognition systems in public spaces, this paper conducts a preliminary review of domestic and international research on frontier technology ethics. It highlights that the potential privacy invasion risks of facial recognition technology, as well as the infringement of personal dignity, cannot be ignored. Research indicates that applying the principle of proportionality and the basic rights rule is crucial for regulating the use of facial recognition technology. To reduce moral risks in technology application and enhance public trust, this paper proposes important recommendations, including restricting the qualifications of entities collecting and processing facial information, clarifying the purpose of use, strictly implementing information processing procedures, and establishing a supervision mechanism. These measures aim to mitigate ethical risks in technology applications, enhance public trust, and promote legislative progress and the refinement of ethical frameworks.